MARRIAGE OF THE LAMPUNG COMMUNITY (MAK DIJEK SIANG TRADITION FROM THE PERSPECTIVE OF LAW NUMBER 16 OF 2019) - Lenny Nadriana; Lina Maulidiana; Idham (Faculty of Law-Universitas Bandar Lampung, 2025)
This study aims to analyze the marriage customs of the indigenous Lampung community, particularly regarding the traditional prohibition (Mak Dijuk Siang) against divorce during one’s lifetime, from the perspective of the Marriage Law. Mak Dijuk Cerai is part of the Lampung customary traditions that govern marriage and uphold high moral values and norms. This research employs legal and social research methods with an empirical approach. Primary data was obtained through interviews and field findings, which were then analyzed using theories relevant to the issues being studied, such as classical texts, books, journals, articles, legal dictionaries, encyclopedias, and previous related research in order to draw conclusions. The results of this study indicate that the Mak Dijuk Siang custom (prohibition of divorce) in the Lampung ethnic community does not conflict with the Marriage Law No. 1 of 1974, as amended by Law No. 16 of 2019 concerning Marriage. The Mak Dijuk Siang custom can be categorized as part of customary law that remains valid and respected in the Lampung community. Moreover, there is no provision in the Marriage Law that explicitly prohibits or regulates this custom. The Mak Dijuk Siang tradition can thus be regarded as part of Indonesia’s cultural and customary legal heritage that remains relevant and applicable within the Lampung community.